Miejsca i Sztuka. Kopaszewo - Prałat, Emilian (Dom Wydawniczy Księży Młyn, 2015)
The choice of Kopaszewo for the second book of the initiated in 2012 a series called Places and art is not accidental. The first was dedicated to the nearby Turew. The fate of the two villages is inseparably bounded by Chłapowski family. Reconstruction of the palace, as well as resettlement of the surrounding park assigned to Augustine Denizot, fulfilled the relations initiated by settling Dezydery's son Stanislaw and later also his doughter Zofia in Kopaszewo, by identical planning solutions in the field of landscape architecture. An example of the Turew and Kopaszewo estates specifically highlights the special role of the manor-house as the mainstay of Polish gentry, a place of preserving a national memory in the new approach, distant from the feudal pattern and close to the organic work attitude. An essential part of the study are detailed analysis of the history of the Kopaszewo palace, the palace chapel and the surrounding park. The study discusses the construction phase of the palace, building equipment including an analysis of the iconographic program of selected rooms and specific indication for the art works which are there. The chapel was elaborated in a particular way. In addition to its history a complete and detailed inventory of temple's equipment catalog is presented for the first time, updated and revised since '70 years of 20th century. A few words are devoted to the nursery habitat founded by Jan Koźmian, which is the second to Podrzecze institution which is the prototype of the modern nursery, created on the initiative of blessed Edmund Bojanowski. Another part of the book is the chapter on palace park designed by Friedrich Teichert and Augustine Denizot. When discussing the history of the garden plans an attempt to bring closer the figures of both these planners. The whole discussion has been set in the context of the history and culture of the Greater Poland over the 17th-21st century. The book ends with a chapter about the figures and roadside shrines located in the village, with particular emphasis on the famous Kopaszewo way of the Cross. Biographies of both Chłapowski family representatives, as well as descriptions of the palace, the chapel and their equipment are accompanied by an extensive photographic material. With regard to the biographies those are unique photographs from the private archive of Chłapowski family. All reflections are supported by archival sources, often published for the first time.
Keywords: Kopaszewo; Miejsca i Sztuka; Chłapowski; Koźmian; Skórzewski